2003
DOI: 10.1074/jbc.m301846200
|View full text |Cite
|
Sign up to set email alerts
|

NMR Studies of Carbohydrates and Carbohydrate-mimetic Peptides Recognized by an Anti-Group B Streptococcus Antibody

Abstract: As part of a program to investigate the origins of peptide-carbohydrate mimicry, the conformational preferences of peptides that mimic the group B streptococcal type III capsular polysaccharide have been investigated by NMR spectroscopy. Detailed studies of a dodecapeptide, FDTGAFDPDWPA, a molecular mimic of the polysaccharide antigen, and two new analogs, indicated a propensity for ␤-turn formation. Different ␤-turn types were found to be present in the trans and cis (Trp-10 -Pro-11) isomers of the peptide: t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 49 publications
1
20
1
Order By: Relevance
“…Although p22 was found much more flexible than p115 or p100c, all three peptides adopted ␤-turn conformations, either of nonclassified type or of type I. This appears to be a rather common conformational feature for short peptides representative of antigenic regions of proteins (85) or polysaccharide antigens such as group A Streptococcus CP (9) and group B Streptococcus CP (38). Indeed, it has been suggested that a ␤-turn allows appropriate exposure of side chain residues for optimal fit within the mAb combining site.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although p22 was found much more flexible than p115 or p100c, all three peptides adopted ␤-turn conformations, either of nonclassified type or of type I. This appears to be a rather common conformational feature for short peptides representative of antigenic regions of proteins (85) or polysaccharide antigens such as group A Streptococcus CP (9) and group B Streptococcus CP (38). Indeed, it has been suggested that a ␤-turn allows appropriate exposure of side chain residues for optimal fit within the mAb combining site.…”
Section: Discussionmentioning
confidence: 99%
“…Ligand Interaction with the Protective mIgAs-Investigation of the molecular pattern of the interactions involved in the peptide-and pentasaccharide-mIgA complexes relied on two complementary methodologies, namely trNOE and STD NMR experiments, whose combination was found to model accurately mAb-ligand interactions (38,47). Indeed, the former technique provides key information on the conformation of the bound ligand, whereas the latter allows epitope mapping via magnetization transfer from the protein to the residues of the ligand that are in close contact with the protein.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural mimicry has been suggested (but not demonstrated) for peptide and carbohydrate ligands of anti-Lewis Y MAb BR55-2, using molecular modeling (52), and proposed for a peptide mimic of the group B streptococcal type III capsular polysaccharide by Pincus and colleagues (53,54). However, structures of both peptide and carbohydrate with the cognate antibody are not available.…”
Section: Discussionmentioning
confidence: 99%
“…Ligand protons that participate in protein binding are subsequently detected and identified with high sensitivity. STD has been successfully applied to identify binding epitopes in multiple systems including peptide/protein, polysaccharide/protein, small molecule/protein and RNA/ small molecule (Johnson et al, 2003;Mayer and James, 2002;Mayer and Meyer, 2001;Pons et al, 2008).…”
Section: Introductionmentioning
confidence: 99%